Use of Latent autoimmune diabetes in adults clinical risk score in type 2 diabetes - Kumar, R. Anil; B. Shetty, Surekha; R, Lalitha (International Journal of Medical Research and Review, 2017)
Background: Subjects with type 2 diabetes may harbour islet auto antibodies and this has implications on progression of disease and therapeutic options. Clinical tools to distinguish antibody positive individuals are essential to guide the therapy. Objective: To develop a clinical risk score in subjects with Type 2 Diabetes to identify LADA. Methods: We studied 100 persons aged between 25 to 65 years diagnosed as Type 2 Diabetes by FBS>126mg/dl and C-peptide >0.6 ng/ml. Results: 17% of Type 2 Diabetic individuals were GAD positive. 11 were males and 6 were females. GAD positivity in the 25 to 34 years age group was 16.3%, 35 to 44 years age group was 20.8%, 45 to 54 years age group was 21.1%, and in >55 was 0% respectively. GAD positivity with respect to the duration of diabetes 0-5 years, 5-10 years and >10 years was 18.2, 12.3 and 20% respectively. 82.4% of GAD positive type 2 diabetes individuals had BMI <25 kg/m2 and age of onset of diabetes <50 years. Mean BMI, waist circumference and fasting C-peptide were 24.86±4.66, 87.55±10.78 and 2.49±1.41 in GAD negative Type 2 Diabetics. Mean BMI, waist circumference and fasting C-peptide were 21.65±3.46, 80.20±10.03 and 3.04±3.66 in GAD positive Type 2 Diabetics. All 17 GAD positive patients had LADA clinical risk score of 2 or more, So this score should be used in the clinic to suspect LADA patients. Conclusions: LADA clinical risk score is ≥2 in all 17 GAD antibody positive subjects with Type 2 Diabetes. So this scoring system can be used as a tool to suspect LADA patients in the clinical setting. A multicentre study is necessary to further validate this scoring system.